The Child In Malaysia: A Review Of Some Of The Laws Determining Status - Siraj, Mehrun (Journal of Malaysian and Comparative Law, 2019)
Malaysia has a multiciplicty of laws that determine the status of rights of the child. This complexity is the result of the somewhat convoluted history of Malaysia’s thirteen component states. An examination of the legal antecedents of the various states reveals the existence of fifteen categories of "laws belonging to, or a legacy from forty-three different systems which have existed from time to time."